Global Systematic Review of Methodological Approaches to Analyze Coastal Shelf Food Webs - Kytinou, Eleni; Sini, Maria; Issaris, Yiannis; Katsanevakis, Stelios (Frontiers in Marine Science, 2020)
The study of marine coastal food webs has a central role in the application of the integrated ecosystem approach for marine management. Changes in food webs caused by natural or anthropic drivers can lead to dramatic shifts in the overall structure and function of coastal marine ecosystems and deterioration of their services. The present review investigates the methodological approaches employed for the assessment of coastal shelf food webs at a global scale and highlights existing gaps and limitations. Out of 1652 published articles that initially met our search criteria, 880 passed the initial screening and 493 were found relevant and were fully analyzed. The information extracted included the spatiotemporal coverage of the studies; the main methodological approaches utilized for the assessment of population state variables (i.e., biomass, size, abundance) and trophic levels; the biotic components and driving factors considered; indices used to describe the structure and functioning of coastal food webs; and main knowledge gaps. Results showed that most studies have been conducted at a subnational level, mostly in the Temperate Northern Atlantic marine realm. Overall, 54% of the studies provided quantitative information on food web structure. The most common methodological approach utilized was modeling (40%), followed by non-experimental-based correlations (30%), and natural or manipulative experiments (14%). Information on population state variables was provided by 69% of the studies, while 42% employed some of the following trophic level determination techniques: stable isotopes, gut contents, fatty acids, and molecular analysis, which were either combined or used in isolation. Specific natural or human drivers were incorporated in 76% of the studies, with fishing being the most common driver. Modeling approaches included multiple indices to describe food web attributes and/or the structure and functioning of coastal shelf ecosystems. Despite the great progress achieved through the development of new tools and techniques, food web analysis still suffers from important knowledge gaps and limitations of the methodological approaches, which are extensively discussed. The present review establishes a useful knowledge base to provide guidance for future research and assessments on coastal shelf food webs, and to support ecosystem-based management.